Direct photoaffinity labeling of Kir6.2 by [gamma-(32)P]ATP-[gamma]4-azidoanilide. - Tanabe, K; Tucker, S; Ashcroft, F; Proks, P; Kioka, N; Amachi, T; Ueda, K (2000)
ATP-sensitive potassium (K(ATP)) channels are under complex regulation by intracellular ATP and ADP. The potentiatory effect of MgADP is conferred by the sulfonylurea receptor subunit of the channel, SUR, whereas the inhibitory effect of ATP appears to be mediated via the pore-forming subunit, Kir6.2. We have previously reported that Kir6.2 can be directly labeled by 8-azido-[gamma-(32)P]ATP. However, the binding affinity of 8-azido-ATP to Kir6.2 was low probably due to modification at 8' position of adenine. Here we demonstrate that Kir6.2 can be directly photoaffinity labeled with higher affinity by [gamma-(32)P]ATP-[gamma]4-azidoanilide ([gamma-(32)P]ATP-AA), containing an unmodified adenine ring. Photoaffinity labeling of Kir6.2 by [gamma-(32)P]ATP-AA is not affected by the presence of Mg(2+), consistent with Mg(2+)-independent ATP inhibition of K(ATP) channels. Interestingly, SUR1, which can be strongly and specifically photoaffinity labeled by 8-azido-ATP, was not photoaffinity labeled by ATP-AA. These results identify key differences in the structure of the nucleotide binding sites on SUR1 and Kir6.2.